Would customers of social enterprises become social entrepreneurs?. (26th October 2022) - Ip, Ching Yin; Liang, Chaoyun
Abstract: To investigate whether customers purchasing goods and services from social enterprises would become social entrepreneurs, 980 survey participants were recruited, and two promising models were tested. In the first study, social entrepreneurial intention (SEI) was investigated by examining the mediating effects of purchase intention and willingness to pay a premium on the relationship between outcome expectation and SEI. The results revealed that the effect of outcome expectation on SEI is mediated through willingness to pay a premium; moreover, purchase intention has no significant effect on SEI. In the second study, we confirmed that the dominant effect on SEI resulted from willingness to pay a premium, followed by outcome expectation. Furthermore, the results revealed that purchase intention enhances the effect of outcome expectation on SEI among customers with high purchase intention, thus demonstrating the moderating role of purchase intention. Business partners could be cultivated through the beneficial outcome expectations and favourable purchasing behaviour exhibited by the customers of social enterprises.